2021
DOI: 10.3389/fmicb.2021.611958
|View full text |Cite
|
Sign up to set email alerts
|

Improved in vitro Efficacy of Baloxavir Marboxil Against Influenza A Virus Infection by Combination Treatment With the MEK Inhibitor ATR-002

Abstract: Currently, all available antiviral drugs against influenza virus (IV) that target the virus proteins directly, like Baloxavir acid (BXA), lead to viral resistance. Therefore, cellular mechanisms and factors essential for IV replication are promising antiviral targets. As IV strongly depends on the virus-induced Raf/MEK/ERK signal pathway for efficient generation of infectious progeny virions, this pathway represents an important target. We aimed to determine whether the MEK inhibitor ATR-002 (PD0184264) is abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…As described previously 34 , MDCK-II cells (American Tissue Culture Collection, catalogue no. CRL-2936) were cultured in 96-well plates and grown overnight at 37 °C in a humidified 5% CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%
“…As described previously 34 , MDCK-II cells (American Tissue Culture Collection, catalogue no. CRL-2936) were cultured in 96-well plates and grown overnight at 37 °C in a humidified 5% CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies also showed that combinations of BXA/BXM and either NAIs or favipiravir had increased antiviral effects against pdmH1N1 and H3N2 IAVs compared with single-drug treatment [55]. BXM-resistant variants emerge readily during treatment with up to 120-fold reduced drug susceptibility (Table 1) [56,57]. The PA I38T mutation has been shown to increase resistance to BXM in vitro and in vivo [58].…”
Section: Baloxavir and Favipiravir To Inhibit Viral Polymerase Activitymentioning
confidence: 96%
“…BXM‐resistant variants emerge readily during treatment with up to 120‐fold reduced drug susceptibility (Table 1) [56,57]. The PA I38T mutation has been shown to increase resistance to BXM in vitro and in vivo [58].…”
Section: Baloxavir and Favipiravir To Inhibit Viral Polymerase Activitymentioning
confidence: 99%
“…This prompted us to analyze whether inhibition of the pathway would also lead to inhibition of SARS-CoV-2 replication. Indeed we could show that zapnometinib (ATR-002, PD 0184264), an oral MEK inhibitor, not only demonstrated antiviral activity against influenza virus 22,23 but also against SARS-CoV-2 in vitro 24 . Interestingly, the inhibitor also led to the reduction of expression of some virus-induced cytokines in infected cells 24 , although the relevance of this observation has still to be examined in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, inhibition of this pathway may interfere with overshooting immune responses. In addition, we previously demonstrated that targeting the cellular Raf/MEK/ERK signaling pathway leads to viral load reduction and protects mice from a lethal viral challenge during infection with another live threatening respiratory virus, the influenza virus [21][22][23] . This prompted us to analyze whether inhibition of the pathway would also lead to inhibition of SARS-CoV-2 replication.…”
Section: Introductionmentioning
confidence: 99%